A new framework for HSE performance measurement and monitoring. (December 2017) - Amir-Heidari, Payam; Maknoon, Reza; Taheri, Bahram; Bazyari, Mahdieh
Graphical abstract: Highlights: A new methodology was introduced for HSE performance measurement. The proposed methodology is based on award and punishment policy. The proposed model combines KPIs selection and aggregation processes. The presented mathematical model is rational and sensitive. The methodology can be a basic to publish an ISO standard. Abstract: Measurement of performance is rooted in quality measurement subject which has been one of the challenging branches of the research in the recent years. Measurement of the performance of an organization in the field of health, safety and environment (HSE) is a prerequisite for continual improvement policy which is the spirit of the new HSE management systems. In this work, after a review of literature, the HSE key performance indicators (KPIs) and frameworks for measurement of HSE performance were reviewed, and a comprehensive classification of KPIs based on three factors (time, scope, and type) was presented. In this research a new framework with an innovative philosophical and mathematical formulation was presented for performance measurement. In the proposed framework, by combination of qualitative and quantitative techniques, a logical selection-aggregation process is performed to determine the performance status from KPIs. The proposed methodology is based on 'award and punishment' policy, and it aggregates the negative and positive performance elements to compute the HSE performance index. In this methodology a lead index and a lag index are calculated and combined to compute the overall HSE index. This methodology was used in a case study for performance measurement in three drilling companies. The results indicated that the model is applicable in the industry for HSE performance measurement and monitoring. The presented framework is risk-related and has 12 special characteristics which makes it possible to use it as a basis for development of an international ISO standard for performance measurement.